PATH44 Corpus callosum diffusion tensor imaging as a biomarker for motor neurone disease. Issue 11 (22nd October 2010) - Filippini, N; Douaud, G; Mackay, C E; Knight, S; Talbot, K; Turner, M R
Abstract : Background: Focality of onset and spread of pathology in MND are poorly understood. Biomarkers are needed to improve diagnosis and therapeutic monitoring, but must accurately reflect the inherent clinical and prognostic heterogeneity. Diffusion tensor imaging (DTI) is a sensitive MRI application for the noninvasive detection of white matter pathology. Methods: High-field cerebral DTI was applied in an unbiased whole-brain analysis across a group of 24 unselected heterogeneous MND patients, and well-matched healthy controls. Patients were scored for clinical upper motor neurone (UMN) involvement, and disability (using the revised ALS Functional Rating Scale, ALSFRS-R). Results: A consistent reduction in fractional anisotropy (FA) was demonstrated in the central corpus callosum (CC) of the MND patients, and correlated with disability. A separate whole-brain analysis in relation to UMN involvement highlighted the corticospinal tract (CST). Conclusions: Corpus callosum FA is a promising biomarker for the heterogeneous syndrome of MND, and may provide a clue to the topographical spread of disease. FA reduction was related to disability, and did not simply reflect UMN involvement, which supports the inclusion of those subjects with apparently LMN/UMN-only phenotypes within one syndrome. The exquisite delineation of the CST in whole-brain analysis of FA in relation to clinical UMN involvement provided validation of both DTI and a "bedside score" as markers of UMN neuronal damage in MND.